Self Regulated Learning dalam Meningkatkan Prestasi Akademik - Sukarman (Politeknik Penerbangan Makassar, 2021)
Learning ability is independent learning, regulating, motivating, with own behavior to set targets for learning (self regulated learning / SRL) and learning outcomes from Makassar Poltekbang cadets. This study aims to determine the effect of self-regulated learning on Makassar Aviation Polytechnic cadets in Pancasila learning. Research on the reasoning ability of cadets is an ability possessed by cadets. One of them is the ability to learn independence in learning, study time, and material search, with data collection techniques in the form of survey research. The results of this study indicate a positive influence on learning motivation. After performing a simple linear regression test with SPSS software, it is known that the tcount value of 16,041 > ttable of 1,678 has an effect on the X variable on the Y variable. It can be concluded that there is an influence (SRL) on the learning outcomes of the Makassar Aviation Polytechnic cadets.